PERBANDINGAN KEMAMPUAN BERPIKIR ALGORITMIK SISWA MENGGUNAKAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING DAN DISCOVERY LEARNING PADA MATERI ALGORITMA DAN PEMROGRAMAN DI KELAS VIII SMP TALENTA JUARA PEKANBARU - Suzrha, Ilza; Novalia, Melly; Al Rian, Rahmad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to compare the algorithmic thinking skills of students who learned using the Problem Based Learning (PBL) model and those who learned using the Discovery Learning (DL) model on the topic of algorithms and programming (Advanced Scratch) at SMP Talenta Juara Pekanbaru. The study was motivated by the fact that students' algorithmic thinking skills in problem-solving were not yet optimal and that the most effective learning model for improving these skills had not yet been identified. This study employed a quantitative approach using a quasi-experimental method with a Non-Equivalent Control Group Design. The sample consisted of 50 eighth-grade students selected through a saturated sampling technique. Data were collected through pretests and posttests and analyzed using the normality test, homogeneity test, independent samples t-test, and N-Gain analysis. The results revealed a significant difference in algorithmic thinking skills between students taught using the PBL model and those taught using the DL model. The average improvement in algorithmic thinking skills in the PBL class was 71.37%, which was higher than that of the DL class (63.59%). Therefore, the Problem Based Learning model was more effective than the Discovery Learning model in improving students' algorithmic thinking skills in learning algorithms and programming.